An Error Analysis on the Use of Simple Present Tense in Descriptive Text - Hikmanisa Bahtiar; Muh. Yusuf Liza (Hasanuddin University, 2022)
The aims of this research include: (1) to identify the types of errors made by 12th grade of the students SMAN 13 Bone in their writing descriptive text, (2) to find out the dominant type of error, (3) to discover the source of error. This research used mix method. The instrument used in collecting the data was writing test. The test was given twice to the students. The population of this research was the 12th grade of the students SMAN 13 Bone. The sample was the 10% of the whole population which consisted of 42 students. In analyzing the data, the researcher found that the students made errors in using simple present tense in writing a descriptive text. The types of errors discovered, namely omission errors, addition errors, misformation errors, and misordering errors. The omission and misformation errors found to be the dominant errors in the students’ writing descriptive text. The sources of errors include Inter-lingual and Intra-lingual transfer.